2006
DOI: 10.1177/1077559506289864
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for Child Neglect: The Case of Adolescent Mothers and Their Children

Abstract: The present study examines the role of neglect potential in adolescent mother-child dyads, both in terms of antecedents and its consequences for children's development. Participants were 100 adolescent mother-child dyads who were part of a larger, longitudinal study. Data were collected from the third trimester of pregnancy until the children's 10th year. Histories of maternal neglect and the quality of mother-child interactions during early childhood were found to predict neglect potential during middle child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 53 publications
1
23
1
Order By: Relevance
“…We also reviewed six studies that did not directly measure maltreatment perpetration by parents, but instead administered a proxy measure, typically the Child Abuse Potential Inventory (CAPI; Milner and Wimberley, 1979, 1980) for use as an outcome (Caliso & Milner, 1992; DiLillo, Tremblay, & Peterson, 2000; Doumas, Margolin, & John, 1994; Lounds, Borkowski, & Whitman, 2006; Narang & Contreras, 2005; Ornduff, Kesley, Bursi, Alpert, & Bada, 2002). The CAPI is designed to estimate the likelihood of a parent physically abusing a child, and can be used as a screening tool to identify families at risk for maltreatment.…”
Section: Review Of the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…We also reviewed six studies that did not directly measure maltreatment perpetration by parents, but instead administered a proxy measure, typically the Child Abuse Potential Inventory (CAPI; Milner and Wimberley, 1979, 1980) for use as an outcome (Caliso & Milner, 1992; DiLillo, Tremblay, & Peterson, 2000; Doumas, Margolin, & John, 1994; Lounds, Borkowski, & Whitman, 2006; Narang & Contreras, 2005; Ornduff, Kesley, Bursi, Alpert, & Bada, 2002). The CAPI is designed to estimate the likelihood of a parent physically abusing a child, and can be used as a screening tool to identify families at risk for maltreatment.…”
Section: Review Of the Evidencementioning
confidence: 99%
“…All of these studies relied on a single reporter, using measures of victimization and potential perpetration taken from the same respondent. There were also several sampling limitations associated with these studies—many had small sample sizes (e.g., Caliso & Milner, 1992; Lounds et al, 2006; Narang & Contreras, 2005), others were taken from non-representative samples (e.g., DiLillo et al., 2000; Doumas et al, 1994, Ornduff et al, 2002), and some utilized data collection techniques typically associated with low participation rates, such as mailed questionnaires and public advertisements (e.g., Doumas et al, 1994). …”
Section: Review Of the Evidencementioning
confidence: 99%
“…Likewise, it is well known that children who have a parent or caregiver suffering from depression or a substance abuse disorder are at risk of being maltreated (Chaffin, Kelleher, & Hollenberg, 1996; Sun, Shillington, Hohman, & Jones, 2001). Many studies have also found that adults who were maltreated during childhood are at risk of maltreating children in their care (e.g., Dixon, Browne, & Hamilton-Giachritsis, 2005; Lounds, Borkowski, Whitman, 2006; Pears & Capaldi, 2001), although other studies have not found strong support for this hypothesis (Fergusson, Boden, & Horwood, 2006; Renner & Slack, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…37,38 In samples of abusive parents, sensitivity was 80% and specificity was 90%. 40 Although developed for adults, it has been used extensively with adolescent parents, 31,35,39,42 pregnant adolescents, 21 and in nonpregnant and nonparent female and male teens. 27,31,38 The psychometric properties when used in adolescents have been questioned, particularly with the use of the clinical cut points and sensitivity and specificity.…”
Section: Dependent Variablementioning
confidence: 99%